Situation Report: Hungary, 26 June 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Difficulties in Recruiting "Gastarbeiter" for the GDR New Facilities for Travel to the West Joint Meeting of the Government and National Council of Trade Unions